2004
DOI: 10.1016/j.ydbio.2003.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Cell migration: Rho GTPases lead the way

Abstract: Rho GTPases control signal transduction pathways that link cell surface receptors to a variety of intracellular responses. They are best known as regulators of the actin cytoskeleton, but in addition they control cell polarity, gene expression, microtubule dynamics and vesicular trafficking. Through these diverse functions, Rho GTPases influence many aspects of cell behavior. This review will focus specifically on their role in cell migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
1,176
0
15

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,284 publications
(1,242 citation statements)
references
References 114 publications
41
1,176
0
15
Order By: Relevance
“…Several identified GAPs and guanine nucleotide exchange factors for Rho proteins have been implicated in cell migration and adhesion (Raftopoulou and Hall, 2004). For instance, DLC1 (deleted in liver cancer), a GAP for Rho proteins, suppresses cell proliferation, migration and invasion in hepatocellular carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several identified GAPs and guanine nucleotide exchange factors for Rho proteins have been implicated in cell migration and adhesion (Raftopoulou and Hall, 2004). For instance, DLC1 (deleted in liver cancer), a GAP for Rho proteins, suppresses cell proliferation, migration and invasion in hepatocellular carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, active Rho is predominantly found at trailing edge of moving cells (Xu et al, 2003), its levels being inversely correlated to the levels of active Rac in many types of cells (Caron, 2003). For this reason, it is believed that, in migrating cells, active Rho forms a gradient inverse to that of Rac and Cdc42 (Raftopoulou and Hall, 2004). Ridley et al (1992) gave the first report of the crosstalk of small G-proteins: they found that Rac is needed for Rho-mediated stress fibre formation and concluded that Rac activates Rho (See also Nobes and Hall (1995)).…”
Section: Spatial Localization and Crosstalk Of Rho Gtpasesmentioning
confidence: 99%
“…Indeed, the inhibition of Rho, through the microinjection of the Rho inhibitor, Clostridium botulinum ADP-ribosyltransferase C3 (C3T), inhibits cell motility in many cell systems [8,9]. Initially, the role of RhoA during cell motility was thought to be restricted to the generation of contractile force and focal adhesion turnover needed for tail retraction [10,11]. This is achieved through its downstream effector, the serine/threonine kinase p160ROCK, which leads to myosin phosphorylation and actin-myosin contractility [12].…”
Section: Introductionmentioning
confidence: 99%